Digital Entrepreneurship by University Students: Insights from a Systematic Literature Review - MOUKRIM, Wiam; OULMOUDNE, Aaziz (European Journal of Science, Innovation and Technology, 2026)
This paper aims to identify the key challenges and research trends related to digital entrepreneurship within the context of university students through a systematic literature review. Specifically, it seeks to explore the barriers, opportunities, and thematic orientations associated with students’ engagement in digital entrepreneurial activities. To achieve this objective, a systematic literature review was conducted using the Scopus database, resulting in a final sample of 119 peer-reviewed articles. In addition, bibliometric and text mining analyses were performed using VOSviewer software (version 1.6.20) to identify thematic structures and research patterns within the selected literature. The findings reveal four major research clusters: (1) behavioral and psychological determinants of entrepreneurial intention, (2) entrepreneurship education and learning processes, (3) strategic opportunities and digital technologies, and (4) creativity, innovation, and self-perception. These clusters highlight the multidimensional nature of digital entrepreneurship among university students. This study contributes to the literature by providing a structured overview of existing research, identifying key gaps, and proposing directions for future research and policy development.